Looking for a Legal Concept of Religious Freedom as Much as Possible Ad Includendum and as Little as Possible Ad Escludendum: Italian and Albanian Constitution Compared - Tokrri, Renata (European Journal of Social Science Education and Research, 2023)
Since ancient times, human beings have sought the spiritual and supernatural dimension, in fact it is believed that freedom of religion can be found in the twelfth edict on stone of Ashoka, which dates back to 250 B.C. ( ). The search for the transcendent has been continuous and has crossed the entire history of man, consequently also the freedom of religion. But what is freedom of religion? With the changes and evolution of modern societies, the concept of religious freedom has also taken on different facets, such as the freedom not to believe, or active atheism, transforming in this way from the freedom of the believer in the freedom of the non-believer. In the Albanian and Italian Constitution, freedom of religion is integrated with freedom of thought, freedom of assembly, etc., since it alone is unable to protect such a broad concept. All this has made it even more difficult to identify the concept. Any attempt to define from the outside the category of religion worthy of protection would go against the provisions of the Constitution which establishes the right of everyone to profess their faith. The analysis carried out will aim to identify who is competent to outline this notion.